Exploring the Role of Parents in Assisting Social Adaptation of Children with Autism in Dhaka City: A Qualitative Study - Sarker, Jiban; Kabir, Humayun (Technium Social Sciences Journal, 2023)
Autism spectrum disorder is a diversity of developmental differences in behavior, communication and social interaction. The children with autism are different from ordinary children. Therefore, this study aims to explore the present situation of autistic children in Dhaka city and also tries to address the strengths and weakness of autistic children. The study also attempts to figure out the fundamental rights enjoyed by autistic children. Besides, to find out the role of parents to adapt autistic children in society is also a target of this study. To fulfill the objectives this study has been framed with qualitative methods where case study, key informant interviews and focus group discussion have been implemented. The children with autism are the part of a family, a society and a nation. Still they are neglected, avoided, underestimated and even considered as a curse. Their qualities are not evaluated. They are supposed to enjoy some fundamental needs. But these needs are not ensured for them properly. As a result, the parents become the sufferer along with the children with autism. Still they play a pivotal role to assist them for social adaptation in Dhaka City.